Case Report: White–Sutton syndrome and cannabidiol, an update on a reported patient with a successful response to off--label therapy - Perilli, Lorenzo; Carbone, Samanta; Minerva, Michele; Rossi, Margherita Maria; Curcio, Maria Rosaria; Lotti, Federica; Grosso, Salvatore (Frontiers in Pediatrics, 2025)
White–Sutton syndrome (WSS), associated with POGZ gene mutations, is a rare genetic disorder characterized by a spectrum of phenotypic features, including intellectual disabilities, developmental delays, and epilepsy. A case report described a female patient diagnosed with WSS who experienced seizures resistant to conventional antiseizure medications. Despite various therapeutic attempts, including valproate, topiramate, levetiracetam, clobazam, rufinamide, and vigabatrin, the patient's seizures persisted. After initiating an off-label treatment with cannabidiol (CBD), the patient achieved complete remission from seizures. Following significant clinical improvement, CBD therapy was discontinued by the parents against medical advice, leading to seizure recurrence. Upon reinstatement of CBD, the patient once again experienced successful seizure control. This report emphasizes the need for further investigation into the off-label use of CBD, as an adjunctive therapy in pediatric individuals with drug-resistant epilepsy associated with WSS. Although CBD shows promise in other epileptic syndromes, this case highlights its potential effectiveness in this specific condition. This manuscript aims to contribute to the understanding of WSS and advocate for further research into novel treatments, particularly the role of CBD in managing epilepsy within this complex clinical context.